The reactive compatibilized effect of SMA for immiscible APA6/PS blends via in-Situ polymerization. (December 2018) - Wang, Wenqi; Bai, Zhiwei; Zhang, Shiping; Guo, Jiahong; Wei, Ting; Wang, Jikui
Abstract: Styrene maleic anhydride (SMA)-g-APA6 copolymer was firstly synthesized by free radical polymerization of styrene and followed by anionic polymerization of ε-caprolactam. The polyamide 6 (APA6)/polystyrene (PS) blends were successfully prepared via anion polymerization. Among in, SMA was acted as both compatibilizer and macromolecular activator. A series of APA6/PS blends with different SMA addition amounts were synthesized to study the effect of SMA on crystallinity, morphology, water resistance, thermal stability and mechanical properties using X-ray diffraction analysis, differential scanning calorimetry, scanning electron microscopy analysis, contact angle measurement, water absorption measurement, molau test, thermogravimetric analysis, stretching and impact test. Correlational analysis proved that the obtained SMA-g-APA6 copolymer has good dispersion with PS. In addition, APA6/PS blends possess good mechanical properties, thermostability and hydrophobic property. Highlights: The caprolactam is a reactive solvent for free radical copolymerization of styrene. The SMA is used as both compatibilizer and macromolecular activator. With the improvement of dispersibility of PS, the mechanical and hydrophobic properties are improved greatly.